Prognostic value of novel imaging parameters derived from standard cardiovascular magnetic resonance in high risk patients with systemic light chain amyloidosis - Arenja, Nisha; André, Florian; Riffel, Johannes; Siepen, Fabian aus dem; Hegenbart, Ute; Schönland, Stefan; Kristen, Arnt; Katus, Hugo; Buß, Sebastian Johannes (Journal of cardiovascular magnetic resonance, 2019)
The differentiated assessment of functional parameters besides morphological changes is essential for the evaluation of prognosis in systemic immunoglobulin light chain (AL) amyloidosis.
Gesehen am 22.04.2020